1989
DOI: 10.1177/37.3.2918221
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-smooth muscle actin, a differentiation marker of smooth muscle cells, is present in microfilamentous bundles of pericytes.

Abstract: a-Smooth muscle (a-sm) actin, an isoform typical of smooth muscle cells (SMC) and present in high amounts in vascular SMC, was demonstrated in the cytoplasm ofpericytes of various rat and human organs by means of immunocytochemistry at the electron microscopic level. In SMC and pericytes, a-sm actin was localized in microfilament bundles, strength-I Supported by the Swiss National Science Foundation, Grants 3.107-0.85 and 3.404.86, and by the Fondation Centre de Recherches M#{233}dicales Carbos et Elsie de Reu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
182
0
4

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(198 citation statements)
references
References 22 publications
12
182
0
4
Order By: Relevance
“…It seems that HIF-1α, although a sustained expression can improve wound healing and revascularization in normal [33] and diabetic mice [42], is more rapidly degraded [43] and displays a reduced activity under hyperglycemic conditions [30,44] due to the methylglyoxylation of its transcriptional cofactor p300. In concordance, we observed that Pecam1 and Acta2, which encode the blood vessel markers CD31 and α-SMA [45,46], were induced in healthy animals 3 and 7 days after wounding after condensate application but less pronounced in diabetic animals. Released VEGF 165 protein -a potent inducer of endothelial cell proliferation and recruitment [45] -seems to be rapidly diluted and degraded [36] and hardly affects Pecam1 expression levels.…”
supporting
confidence: 68%
“…It seems that HIF-1α, although a sustained expression can improve wound healing and revascularization in normal [33] and diabetic mice [42], is more rapidly degraded [43] and displays a reduced activity under hyperglycemic conditions [30,44] due to the methylglyoxylation of its transcriptional cofactor p300. In concordance, we observed that Pecam1 and Acta2, which encode the blood vessel markers CD31 and α-SMA [45,46], were induced in healthy animals 3 and 7 days after wounding after condensate application but less pronounced in diabetic animals. Released VEGF 165 protein -a potent inducer of endothelial cell proliferation and recruitment [45] -seems to be rapidly diluted and degraded [36] and hardly affects Pecam1 expression levels.…”
supporting
confidence: 68%
“…Generally, MLCK is known to phosphorylate the serine-19 residue of myosin regulatory light chain, which would enhance the actomyosin contraction via the RhoA pathway [33,34]. SMA is localized in microfilament bundles, strengthening the contraction of smooth muscle cells, but not in cardiac myocytes [35,36]. ACTA1 is a major constituent of the contractile apparatus, which can be found in skeletal muscle, but poorly expressed in cardiac myocytes [37].…”
Section: Resultsmentioning
confidence: 99%
“…[1618] The results of this study showed that massive ROS was produced after exposure to PQ, which indicated strong oxidative stress on the cells. UTI could significantly reduce the increase of ROS induced by PQ, and the effect was stronger as the concentration of UTI increased.…”
Section: Discussionmentioning
confidence: 99%